Jane Austen’s Treatment of Love and Marriage In Pride and Prejudice That Becomes the Theme of Gender Injustice: A Review: Exploring the Complexities of Love, Marriage, and Gender Inequality in Jane Austen's Pride and Prejudice (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The objective of this research paper is to look at the ways in which the contemporary realities of women's life and their position in society inform the treatment of these aspects in the article. This article seems to hold mixed views about marriage, seeing it as a culmination of woman's development but also as a diminishment. Though the words identified in Jane Austen's work with the right marriage are affection and esteem, even where these were present in life, things were often different. The reality of marriage for most women in the eighteenth century also meant repeated childbirth with the attendant physical comfort, followed by years spent in child_ rearing. The use of marriage as one of the two most common conventional endings in fiction provides a sense of closure, and makes it possible to bring together the themes and depiction of private and public life. Women were extremely dependent on marriage, and their education aimed at preparing them for this role alone by teaching them skills considered to make them more attractive to men.